ANALISIS HASIL TANGKAPAN IKAN TUNA MADIDIHANG BERDASARKAN MUSIM DI PERAIRAN KEPULAUAN TANIMBAR - Fuatkait, Danyel Selwanus; Matrutty, Delly D P; Waileruny, Welem (Departement of Aquatic Resources Management, Fisheries and Marine Science Faculty, Pattimura University, 2022)
Yellowfin tuna is an important economic commodity that is widely exploited with various fishing tools and methods and catches of various sizes. This study aims to describe yellowfin tuna fishing units and analyze the size distribution and productivity of yellowfin tuna resources based on seasons in the waters of the Tanimbar Islands. This research was carried out in the waters of the Tanimbar Islands from August 2021-March 2022. Data were collected through interviews, observations and measurements of the length and weight of the catch and analyzed descriptively and CPUE analysis. The results showed that catching yellowfin tuna in the waters of the Tanimbar Islands was classified as a small-scale fishery, using hand fishing gear with boat sizes under 10 GT. Yellowfin tuna caught in the waters of the Tanimbar Islands throughout the year are dominated by small size fish that are still classified as juveniles. The presence of large-sized tuna was more in the first transitional season with an attendance percentage of 21.98%. The abundance of yellowfin tuna resources in the waters of the Tanimbar Islands fluctuated according to the seasons, and the highest abundance was found in the transitional season one. ABSTRAK Ikan tuna madidihang merupakan komoditas ekonomis penting yang banyak dieksploitasi dengan berbagai alat dan metode penangkapan serta hasil tangkapan yang beragam ukurannya. Penelitian ini betujuan untuk mendeskripsi unit penangkapan tuna madidihang dan menganalisis distribusi ukuran serta produktivitas sumberdaya ikan tuna madidihang berdasarkan musim di perairan Kepulauan Tanimbar. Penelitian ini dilaksanakan di perairan Kepulauan Tanimbar sejak Agustus 2021-Maret 2022. Data dikumpulkan melalui wawancara, observasi dan pengukuran panjang dan berat hasil tangkapan, kemudian dianalisis secara deskriptif serta analisis CPUE. Hasil penelitian menunjukkan bahwa penangkapan ikan tuna madidihang di perairan Kepulauan Tanimbar tergolong perikanan skala kecil, menggunakan alat tangkap pancing tangan dengan ukuran kapal di bawah 10 GT. Ikan tuna madidihang yang tertangkap di perairan Kepulauan Tanimbar sepanjang tahun didominasi ikan ukuran kecil yang masih tergolong juvenile. Kehadiran ikan tuna ukuran besar lebih banyak pada musim peralihan satu dengan persentasi kehadiran sebesar 21,98%. Kelimpahan sumberdaya ikan tuna madidihang di perairan Kepulauan Tanimbar berflutuksi menurut musim, dan kelimpahan tertinggi didapati pada musim peralihan satu Kata kunci: Distibusi ukuran, kelimpahan, musim, pancing tangan, tuna madidihang